Quantitative Performance of Krui Cattle in Traditional Farming in Krui Selatan and Pesisir Selatan District, Pesisir Barat Regency, Lampung - Kurniawati, Dian; Dakhlan, Akhmad; Adhianto, Kusuma; Rafian, Teguh (AGRITROPICA : Journal of Agricultural Sciences, 2025)
The objective of this study was to evaluate the quantitative performance of thirty-six Krui cattle aged 18 to 36 months, raised on a traditional farm located in the Krui Selatan and Pesisir Selatan district, Pesisir Barat Regency, Lampung. A survey method using purposive sampling was employed to collect the samples. Body measurements, including body weight (BW), body length (BL), chest width (CW), chest circumference (CC), chest depth (CD), and hip circumference (HC), were recorded. The collected data were analysed descriptively. The findings revealed that BW, BL, CW, CC, CD, and HC of the Krui cattle in Krui Selatan District were: 175.40 ± 41.77 kg, 111.18 ± 5.74 cm, 28.18 ± 2.56 cm, 138.55 ± 16.88 cm, 52.73 ± 8.19 cm, and 18.00 ± 1.41 cm, respectively. At the same time, the Krui cattle's BW, BL, CW, CC, CD, and HC in Pesisir Selatan District were 154.23 ± 65.70 kg, 110.64 ± 9.36 cm, 24.86 ± 5.15 cm, 120.80 ± 11.2 cm, 47.67 ± 5.33 cm, and 17.64 ± 1.36 cm, respectively. This study concludes that the quantitative performance of Krui cattle in Traditional Farming in Krui Selatan District is greater than that of Krui cattle in Pesisir Selatan District. Still, more miniature compared to other local cattle breeds (Madura cattle, Bali cattle, Aceh cattle, Ongole grade cattle, and Jabres cattle) in Indonesia.